Giulio Preti Intellettuale critico e filosofo attuale - Cambi, Franco; Mari, Giovanni (Studi e saggi, 2011)
In the period following the Second World War Giulio Preti was one of the leading exponents of Italian philosophy. A master of open critical thought, cultivated in the light of a rationalism that dialogued with, and integrated into his own philosophical model, many of the currents and stances of the global research scenario. Phenomenology, Marxism, pragmatism, neopositivism, transcendentalism and structuralism: in Preti all of these found an organic and original synthesis. Further, his particular brand of rationalist-critical thought touched on many aspects of philosophical knowledge: theoretical philosophy, the philosophy of science, that of language and that of art, from ethics to politics and even taking in the history of philosophy, offering authoritative contributions in every sphere. One hundred years after his birth, the University of Florence and the heir to the Faculty in which he lectured at length, the Faculty of Education, has decided to honour his memory with this anthology of studies, penned by former pupils and others and also by younger scholars, to once again focus the wealth of this thought and its, in many respects, current relevance. Even now, this particular brand of open, critical rationalism can offer a benchmark for addressing the new issues for philosophical reflection thrown up by modern society and culture.